Prinsip dan Faktor Yang Mempengaruhi Kurikulum Merdeka - Awalludin Awalludin; Nur Aisyah; Indah Cahyani; Mustafiyanti Mustafiyanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Merdeka Curriculum is designed with several basic principles as its foundation, such as learning that is simpler and deeper, more independent, and more relevant and interactive. It is hoped that these principles can make the teaching and learning process more effective and interesting for students. However, in its application, there are several factors that can influence the study of the Independent Curriculum. These factors include challenges in implementation, changes needed in the current education system, and how to accelerate the development and development of this curriculum. Therefore, it is important to examine the principles and factors that influence the Independent Curriculum. It is hoped that this study will provide a better understanding of how these principles and factors influence the implementation of the Independent Curriculum, as well as what challenges may be faced in its implementation.